Oxygen therapy does not increase production and damage induced by reactive oxygen species in focal cerebral ischemia - Sun, Li; Wolferts, Guido Peter Maximilian; Veltkamp, Roland (Neuroscience letters, 2014)
Oxygen therapy with hyperbaric oxygen (HBO) or normobaric hyperoxia (NBO) improves outcome in experimental cerebral ischemia. However, an increased formation of reactive oxygen species (ROS) may be an undesirable side effect of oxygen therapy. We investigated the effect of both oxygen therapies on ROS production and adverse effects in murine focal ischemia. 25min after 90min filament-induced middle cerebral artery occlusion (MCAO), mice breathed either air, 100% O2 (NBO), or 100% O2 at 3 ata (HBO) for 60min. ROS were depicted on tissue sections after preischemic injection of hydroethidine, a marker of in vivo superoxide production. Moreover, infarct sizes were quantified in experiments using peroxybutinitrite (PBN) in mice treated with HBO. Effects of oxygen therapy were also tested in superoxide 2 knock-out mice. Both NBO and HBO significantly reduced superoxide radicals compared to air. Application of PBN had no additional protective effect when combined with HBO. Infarct volumes did not differ among SOD2 knock-out mice receiving air (34.0±19.6mm3), NBO (35.4±14.3mm3) or HBO (33.4±12.2mm3). In conclusion, brief episodes of oxygen therapy do not appear to promote damage inflicted by ROS in experimental stroke.